ASSESSMENT OF KNOWLEDGE AND SELF-MEDICATION PRACTICE OF DYSMENORRHEA AMONG PHARMACY UNDERGRADUATE STUDENTS: A CROSS-SECTIONAL STUDY - Rahmi, M.Sc, Eldiza Puji; Ananda, Bella; Prabowo, Imam; Pradana, Dhigna Luthfiyani Citra (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2023)
Dysmenorrhea is pain during menstruation that is experienced during adolescence caused by uterine muscle spasms. Data on knowledge of dysmenorrhea and self-medication practice among undergraduate student at Universitas Pembangunan Nasional Veteran Jakarta (UPN Veteran Jakarta) are scarce. This study aimed to assess and determine the relationship between the level of knowledge and primary dysmenorrhea self-medication practice. A cross-sectional study was carried out among female undergraduate Pharmacy Student of UPN Veteran Jakarta. A total of 107 unmarried and nulliparous female students were included in this study using the stratified random sampling technique. Based on the results of the study, 47 students (43.9%) had adequate knowledge, 46 students (43.0%) had moderate knowledge, and 14 students (13.1%) had inadequate knowledge. Forty female students (37.4%) had good practice, 40 female students (37.4%) had moderate practice, and 27 female students (25.2%) had poor practice regarding dysmenorrhea, and in this study, the value of confidentiality (p< 0.05). It is considered significant, with the intention that there is a relationship between the level of knowledge and primary dysmenorrhea self-medication.